Study on Dynamics Simulation of RV Reducer based on Rigid-flexible Coupling - Qiu Tao Du Qungui (Jixie chuandong)
RV reducer has the characteristics of large transmission ratio, large carrying capacity, high transmission accuracy and stable transmission, so it is of great significance to research its dynamic characteristics. A RV reducer is taken as the research object, and the parametric three-dimensional model is established in SolidWorks. The rigid-flexible coupling dynamics model of RV reducer is established by Abaqus and Adams. Through simulation analysis, the dynamic response curve and transmission error of key components are obtained. Through spectrum analysis, the main factor affecting the transmission accuracy is the pure torsional elastic deformation of the crankshaft. The research method has certain guiding significance for precise design of RV reducer.